Pathology and molecular mechanisms of Schistosoma japonicum-associated liver fibrosis - Liu, Zhilong; Zhang, Lichen; Liang, Yinming; Lu, Liaoxun (Frontiers in Cellular and Infection Microbiology, 2022)
Schistosomiasis has been widely disseminated around the world, and poses a significant threat to human health. Schistosoma eggs and soluble egg antigen (SEA) mediated inflammatory responses promote the formation of egg granulomas and liver fibrosis. With continuous liver injuries and inflammatory stimulation, liver fibrosis can develop into liver cirrhosis and liver cancer. Therefore, anti-fibrotic therapy is crucial to increase the survival rate of patients. However, current research on antifibrotic treatments for schistosomiasis requires further exploration. In the complicated microenvironment of schistosome infections, it is important to understand the mechanism and pathology of schistosomiasis-associated liver fibrosis(SSLF). In this review, we discuss the role of SEA in inhibiting liver fibrosis, describe its mechanism, and comprehensively explore the role of host-derived and schistosome-derived microRNAs (miRNAs) in SSLF. Inflammasomes and cytokines are significant factors in promoting SSLF, and we discuss the mechanisms of some critical inflammatory signals and pro-fibrotic cytokines. Natural killer(NK) cells and Natural killer T(NKT) cells can inhibit SSLF but are rarely described, therefore, we highlight their significance. This summarizes and provides insights into the mechanisms of key molecules involved in SSLF development.